Investigating the behavior of various cocatalysts on LaTaON2 photoanode for visible light water splitting. Issue 1 (5th December 2016) - Si, Wenping; Pergolesi, Daniele; Haydous, Fatima; Fluri, Aline; Wokaun, Alexander; Lippert, Thomas
Abstract : NiO x, Ni0.7 Fe0.3 O x, CoO x and IrO x were loaded as cocatalysts on LaTaON2 photoanode to improve the photoelectrochemical performance for water splitting. Abstract : We performed a comparative study on the photoelectrochemical performance of LaTaON2 loaded with NiO x, Ni0.7 Fe0.3 O x, CoO x and IrO x as cocatalysts. Ni-based oxides lead to the highest improvement on the photoelectrochemical performance, while CoO x and IrO x also enhance the performance though to a lower extent, but they simultaneously introduce more pseudocapacitive current thus resulting in an inefficient utilization of the photo-generated holes. Repetitive voltage cycling between 1.0 VRHE and 1.6 VRHE transforms the NiO x and Ni0.7 Fe0.3 O x into oxyhydroxides known to possess higher catalytic activities. However, these oxyhydroxides lead to lower photoelectrochemical performance compared to the as-loaded oxides, most probably due to the decay of the passivation centers at the photoelectrode–cocatalyst interface. High catalytic activities cannot be achieved without sufficient passivation of surface recombination states. Despite that the photoelectrochemical performance of LaTaON2 can be improved by cocatalysts, the maximum achievable photocurrent density is still not comparable to that reported for other oxynitride compounds. Our study suggests that poor electronic conductivity or severe bulk recombination of the photo-generated electron–hole pairs are the main limiting factors for the photon-to-current conversion efficiency in LaTaON2 photoanodes.